2017
DOI: 10.1200/jco.2017.35.4_suppl.758
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios as predictive and prognostic markers in patients with locally advanced rectal cancer treated with neoadjuvant chemoradiation.

Abstract: 758 Background: A standard therapy for locally advanced rectal cancer (LARC) includes fluoropyrimidine (FP)-based neoadjuvant chemoradiation (nCRT). Previous studies have inconsistently demonstrated that baseline neutrophil- and platelet-to-lymphocyte ratios (NLR and PLR) are predictive of response to nCRT or prognostic of outcomes in LARC. Methods: We performed a review of patients with LARC undergoing nCRT followed by surgery with curative intent from 2005-2013 in 3 academic cancer centers from 2 Canadian p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Reasonable attempts were made to request unreported HR or 95% CI data from the authors. As a result, one additional study 34 was included in the analysis with this information provided.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Reasonable attempts were made to request unreported HR or 95% CI data from the authors. As a result, one additional study 34 was included in the analysis with this information provided.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Andras et al [23] reported that NLR is a simple and cost-effective marker for predicting neoadjuvant treatment response in LARC, with a cut-off value of 4.5. In contrast, Dudani et al [25] analyzed 1,237 rectal cancer patients who underwent neoadjuvant CRT, and showed that neither pretreatment PLR nor NLR predicted pCR. However, some studies have focused on changes in serologic markers before and after neoadjuvant CRT.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, there have been several studies showing that pretreatment serologic markers are not related to the survival rate of rectal cancer patients who underwent neoadjuvant CRT followed by curative resection. Dudani et al [25] conducted a study by setting the cut-off values of PLR and NLR to 150 and 4, respectively, and reported that PLR and NLR were not independent prognostic factors of DFS or OS. Portale et al [11] found neither PLR nor NLR to be associated with survival in rectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the predictive value of baseline systemic inflammatory responses. Dudani et al ( 31 ) reviewed 1,527 patients with rectal cancer receiving nCRT and surgery, and revealed that NLR and PLR were not predictors for disease-free survival or overall survival, and could not predict pCR. Additionally, Shen et al ( 29 ) reported that there was no significant association between tumor response and NLR to nCRT.…”
Section: Discussionmentioning
confidence: 99%